2014
DOI: 10.1155/2014/387912
|View full text |Cite
|
Sign up to set email alerts
|

Marker-Assisted Selection for Recognizing Wheat Mutant Genotypes Carrying HMW Glutenin Alleles Related to Baking Quality

Abstract: Allelic diversity of HMW glutenin loci in several studies revealed that allelic combinations affect dough quality. Dx5 + Dy10 subunits are related to good baking quality and Dx2 + Dy12 are related to undesirable baking quality. One of the most regular methods to evaluate the baking quality is SDS-PAGE which is used to improve baking quality labs. Marker-assisted selection is the method which can recognize the alleles related to baking quality and this method is based on polymerase chain reaction. 10 pairs of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Different subunits were identified by the mobility on SDS-PAGE, but there was not always consistent agreement between molecular weight and mobility in SDS-PAGE method, and because of close position of Dx2 and Dx5 on the gel, accurate identification was complicated. The identification of these alleles using specific PCR primers was precise and straightforward (Jin et al, 2011;Zamani et al, 2014). However, functional markers were not developed for the majority of rare HMW-GS alleles, such as Glu-D1j, Glu-D1b, which can be determined by SDS-PAGE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different subunits were identified by the mobility on SDS-PAGE, but there was not always consistent agreement between molecular weight and mobility in SDS-PAGE method, and because of close position of Dx2 and Dx5 on the gel, accurate identification was complicated. The identification of these alleles using specific PCR primers was precise and straightforward (Jin et al, 2011;Zamani et al, 2014). However, functional markers were not developed for the majority of rare HMW-GS alleles, such as Glu-D1j, Glu-D1b, which can be determined by SDS-PAGE.…”
Section: Discussionmentioning
confidence: 99%
“…Application of DNA markers also allows discrimination between homo-and heterozygous plants. Use of DNA markers increases the efficiency and speed of the development of improved cultivars, and the method is becoming a standard and reliable technology in breeding for higher baking quality (Ahmad, 2000;Ma et al, 2003;Gale, 2005;Kocourková et al, 2008;Liang et al, 2 010;Polishchuk et al, 2010;Jin et al, 2011;Liu et al, 2012;Rasheed et al, 2014;Zamani et al, 2014;Tian et al, 2015;Khlestkina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression from these protein families occurs early in grain development 16 , 23 . Zamani et al 24 and Izadi-Darbandi et al 25 reported that mutant, “O-64.1.10” and its parent, “Omid” wheat cultivar have two HMW-GS genes, Dx2 + Dy12 and Bx7 + By8 but the improvement of baking quality in the mutant, “O-64.1.10” was unknown. A negative effect of Dx2 + Dy12 was published previously by several studies 26 31 .…”
Section: Introductionmentioning
confidence: 99%